Financial rehabilitation of export enterprises in developing countries - International Trade Centre UNCTAD/GATT (Geneva : International Trade Centre UNCTAD/GATT, 1987)
It discusses typical problems arising in export oriented enterprises, measures to avoid them; steps of the rehabilitation process; special considerations relating to small scale export oriented enterprises.
ucj, 15/01/2019
Loans
Keywords: Developing countries; Exports--Finance; Manufacturing industries--Finance